سید محمدّوجیہہ السیما عرفانی بطور مداحِ اہل بیت(شاعرانہ تناظر میں) (Al-Aasar, 2025)
Syed Muhammad Wajih-us-Seema Irfani (1920 - 1991 AD) is regarded as a renowned scholar, Broadcaster, Poet , Writer and Translator. He devoted his life to the service of religion and knowledge. He was born in Gojar Khan District Rawalpindi and remained actively associated with journalism from 1941 to 1991. During this period, he wrote columns, editorials, and articles for various newspapers and magazines.His scholarly and intellectual interests included religious studies, social sciences, poetry, and literature. Along with journalism, he also remained associated with Radio and PTV. His writings reflect depth of thought, clarity of expression, and intellectual balance.Among his special distinctions is that he was one of the first Pakistani scholars to introduce modern methods of religious interpretation and intellectual discourse. Through his writings, he conveyed religious teachings in a simple, effective, and contemporary manner. He had a remarkable ability to relate religious thought to modern intellectual and social issues, which earned him a distinguished position among scholars. His poetry is full of Affection and devotion of the Ahl al-Bayt and it is the cause of lighting a candle in the hearts of the readers. This article sheds light on the praise of Ahl al-Bayt in a poetic context.